Alih Teknologi Aklimatisasi Bibit Pisang Kultur Jaringan Berbasis Konsepsi PHPT Bagi KWT Sauyunan dan Poktan Sabilulungan - Tini Sudartini; Adam Saepudin; Elya Hartini; Gilang Vaza Benatar; Ida Hodiyah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The Sauyunan Women Farmers Group and the Sabilulungan Farmers Group face obstacles in meeting the demand for quality banana seeds. They usually get banana seedling propagated conventionally with the consequence that production is not optimal because of many deficiencies. Moreover, their knowledge about banana pests and diseases and their management is still lacking. These challenges were answered by providing counseling and technology transfer of acclimatization of tissue culture banana seeds based on the concept of integrated pest and disease management. The programs was attended by 23 participants who were group members and a Field Instructor Officers of Tamansari District. Participants were given counseling on the economic potential of bananas, banana tissue culture seedling, acclimatization, and types of banana pests and diseases and their management in an integrated manner. In addition, technology transfer of tissue culture banana seedling acclimatization was provided through training methods which included preparing media, planting seeds (acclimatization), handling, transplanting, as well as observation and monitoring. Thus, participants were given insight and skills in responding to the supply of quality banana seeds needed in an effort to increase their income through this program.